Irradiation-responsive polysulfone film as a colorimetric UVA/UVB differentiator. Issue 15 (5th April 2023) - Monteiro, Bernardo; Leal, João Paulo; Outis, Mani; Casimiro, Maria Helena; Pereira, Cláudia C. L.
Abstract : This research work presents a photochromic flexible film, for fast and real-time detection and differentiation of UVA and/or UVB radiation. The host–guest system was produced by confining 7% (w/w) of a highly fluorinated ionic liquid in polysulfone. Abstract : A wearable, small size, flexible and energy consumable free colorimetric detector of UVA radiation and UVB/UVA differentiation was created based on the peculiar stimuli-responsive behaviour of an imidazolium based ionic liquid. Semi-transparent polysulfone films are transformed into opaque and homogenous red films under UVA radiation (315–360 nm), while lower wavelength exposure (280–315 nm) induces increased emission detectable under dark light, with no colour modification of the film under visible light. Thermal analysis (TGA and DSC), spectroscopic analysis (FT-IR, 1 H-NMR and UV-Vis), scanning electronic microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) were conducted to elucidate confinement mechanism and irradiation effects.